2017
DOI: 10.5455/apd.274483
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Attitude Scale toward the Violence among University Students

Abstract: 0.91, 0.87, 0.83, 0.83, 0.73, 0.75

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Işıker (2011) emphasizes that aggression and violence are words used interchangeably, violence is a qualitative and more damaging state of aggression based on feelings such as hatred, anger, and aggression, and aggression is a broader and higher concept that includes violence. In their research, Adıbelli, Saçan, and Türkoğlu (2018) drew attention to the individual and social effects of violence, such as reducing individuals' self-confidence and preventing their social development by causing them to have feelings such as fear, anxiety and vulnerability and they stated that violence is an important social problem that needs to be handled in a multidimensional way and to be tackled multidisciplinary. Işıker (2011) emphasizes that every person experiences a feeling of violence from time to time, but that individuals who control this feeling and prevent it from turning into a behavior avoid violent behavior, that the feeling of violence is natural, the unnatural situation is the transformation of this feeling into behavior.…”
Section: Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Işıker (2011) emphasizes that aggression and violence are words used interchangeably, violence is a qualitative and more damaging state of aggression based on feelings such as hatred, anger, and aggression, and aggression is a broader and higher concept that includes violence. In their research, Adıbelli, Saçan, and Türkoğlu (2018) drew attention to the individual and social effects of violence, such as reducing individuals' self-confidence and preventing their social development by causing them to have feelings such as fear, anxiety and vulnerability and they stated that violence is an important social problem that needs to be handled in a multidimensional way and to be tackled multidisciplinary. Işıker (2011) emphasizes that every person experiences a feeling of violence from time to time, but that individuals who control this feeling and prevent it from turning into a behavior avoid violent behavior, that the feeling of violence is natural, the unnatural situation is the transformation of this feeling into behavior.…”
Section: Violencementioning
confidence: 99%
“…In the review of the literature; It is observed that studies mostly focus on domestic "violence", "violence against women", "violence at school", "violence at work", "violence against children". And it was also observed that the studies to determine the perceptions, the attitudes and the tendencies of children, adolescents, youth and high school and university students regarding violence (Adıbelli, Saçan, & Türkoğlu, 2018;Akın, Yıldız and Basha, 2016;Atman, 2003;Avcı and Yıldırım, 2014;Ayan, 2007;Demirbağ Bolat, S., 2010;Özgür, Yörükoğlu and Baysan-Arabacı, 2011;Özkan et al, 2018;Pehlivan, 2008;Tunay and Soygüt, 2009;Vahip and Doğanavşargil, 2006). As for the review of the literature on violence in sports; it is seen that violence in sports is approached mostly with the dimensions of violence and sports culture in society, factors affecting violence and aggression, fan violence and fanaticism, football and violence, and it is also seen that the scale adaptation studies or the scale development studies carried out to determine the perceptions, attitudes and tendencies of people in different education and age groups and athlete groups towards violence in sports (Bulgu, 2005(Bulgu, , 2012Ayan, 2007;Eraslan et al, 2019;Özen, Kabakuş, & Eygü, 2013;Var and Cihan, 2019).…”
Section: Sport and Violencementioning
confidence: 99%